Pengaruh Budaya Organisasi terhadap Kinerja Karyawan Melalui Motivasi pada PT Logistik Palletindo Group - Maysaroh Maysaroh; Supardi Supardi; Agus Dharmanto (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study aims to measure the direct effect and indirect effect of organizational culture on employee performance through motivation. This study uses quantitative research methods with the subject of PT Logistics Palletindo Group employees. The population in this study were 57 employees and the sample size was 57 respondents using the saturated sampling technique formula. The design used in this study is hypothesis testing using the statistical tool SPSS version 26. The results showed that organizational culture affects employee performance with a t value of 3.416> 2.00404, organizational culture affects motivation with a t value of 3.664> 2.00404, motivation affects employee performance with a t value of 11.814> 2.00404, and the indirect effect of organizational culture on employee performance through motivation has a significant effect with a total effect value greater than the direct effect of 0.375> 0.793.